2018
DOI: 10.1016/j.jcrs.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pseudophakic refractive error: Interplay of biometry prediction error, anterior chamber depth, and changes in corneal curvature

Abstract: The Universal II and RBF methods were better than SRK/T in medium length eyes (22 to 24.5 mm). It might be prudent to expect a progressive hyperopic shift in the 3 months after surgery because of posterior IOL migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…As found in our previous study [7], there is a hyperopic tendency at both postoperative assessments with the EDOF IOL (Fig. 4), which may be due keratometric changes or to the IOL moving posteriorly due to capsular contractions [18,19], and direct assessment of IOL shift would further help explain the cause. Adjustments have since been made to the biometry A-constants to optimize the postoperative refractive outcomes in our clinic.…”
Section: Discussionsupporting
confidence: 66%
“…As found in our previous study [7], there is a hyperopic tendency at both postoperative assessments with the EDOF IOL (Fig. 4), which may be due keratometric changes or to the IOL moving posteriorly due to capsular contractions [18,19], and direct assessment of IOL shift would further help explain the cause. Adjustments have since been made to the biometry A-constants to optimize the postoperative refractive outcomes in our clinic.…”
Section: Discussionsupporting
confidence: 66%
“…Wallace et al investigated keratometric changes after clear corneal incision cataract surgery and found a tendency for the cornea to steepen by an average of 0.11D between weeks 1 and 4 postoperatively. 4 Vass et al, however, found that changes in corneal topography between 1 week and 1 year after cataract surgery were negligible. 12 Information on this topic is limited particularly regarding changes that occur in the very early post-operative period.…”
Section: Discussionmentioning
confidence: 97%
“…Fluctuation in ACD after cataract surgery has been reported by other authors although the direction of IOL shift has been variable with some reporting an anterior (myopic) shift 7,8 instead of a posterior (hyperopic) shift. 4,8 Despite the uncertainty in direction of the shift, ACD fluctuation is likely a major contributor to changes in postoperative UCVA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations